THE IMPORTANCE OF ANALYSIS AND COOPERATION IN ENSURING SAFE TOURISM - Alieva Mahbuba Toychievna (European Journal of Life Safety and Stability (2660-9630), 2021)
This article explores the importance of analysis and cooperation in ensuring safe tourism, as well as the problems and ways of ensuring the safety of tourists. At the same time, proposals were made on the main factors of the tourism industry, the specifics of its development, environmental protection of the local population and measures.